Efforts to Control Blood Pressure for Prolanis Hypertension Members through the Utilization of Bay Leaf Decoction - Handayati, Anik; Suhariyadi; Pestariati (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2025)
Bay leaves are a type of kitchen spice that is often added to dishes, inexpensive, and easily obtained. Research results have proven that the active compounds in bay leaves are quite effective and safer in lowering blood pressure. Most of the Sreseh residents work as fishermen who tend to consume salty foods, which causes a high incidence of hypertension. Therefore, it is necessary to increase knowledge about healthy lifestyles and the use of herbal medicine made from boiled bay leaves to lower blood pressure among Prolanis hypertension members in the Sreseh Health Center area. The methods used in this community service activity are lecture/presentation and demonstration methods. Lecture activities are carried out by delivering material on the prevention and natural treatment of hypertension using bay leaves, the benefits of bay leaves, and the processing of bay leaves for hypertension treatment. The demonstration method is carried out by showing how to process bay leaves. The target of the activity is Prolanis hypertension patients in Noreh Village, within the working area of the Sreseh Health Center, Sampang, Madura. Members of the Chronic Disease Management Program (PROLANIS), especially those with hypertension, were very enthusiastic and motivated to participate in every stage of the community service activity, from blood pressure checks, Prolanis exercises, to education on the benefits of bay leaves. After consuming boiled bay leaves, blood pressure checks on Prolanis members with hypertension showed a 30% decrease in the number of Prolanis members with hypertension, from the previous 76.67% to 46.67%.